Conversational Skills And Their Activation In And Outside The Classroom - Makhamadkhodjaev Bakhromkhodja (Euro Asian Journal Publishing, 2024)
This scientific article examines the importance of conversational skills in teaching a foreign language and the methods of its activation both in the classroom and beyond. The article provides an overview of theoretical approaches to conversational skill, as well as an analysis of various methods of its activation. The main focus is on practical methods and techniques that teachers can use to stimulate students' conversational skills. The article also presents the results of a study of the effectiveness of these methods. In conclusion, the importance of regular practice and continuous improvement for the successful development of conversational skills is emphasized.
Keywords: teaching; foreign language; school; conversational skill